Identity conflicts among Oriental Christian in Sweden - Gaunt, David (Sens public)

(untitled) (Département des littératures de langue française, 2010)
This article deals with the Assyrian, Chaldean and Syrian Orthodox immigrants to Sweden. They form a large group coming mostly from Turkey, Syria, Lebanon and Iraq. From the start they have had complicated relations with the Swedish government and needed to navigate the country’s ever changing immigration and integration policies. The demands of living in diaspora has also aided in splitting the group into two rival sections. One calls itself “Assyrians” and is basically modernist and secular in orientation. The other calls itself “Syrian” and is basically traditionalist and religious in orientation. This bifurcation has had many consequences for the ability of the group to make an impact on the surrounding Swedish society.